Low-Dose Iron Supplementation in Infancy Modestly Increases Infant Iron Status at 9 Mo without Decreasing Growth or Increasing Illness in a Randomized Clinical Trial in Rural China. Issue 3 (20th January 2016) - Lozoff, Betsy; Jiang, Yaping; Li, Xing; Zhou, Min; Richards, Blair; Xu, Guobin; Clark, Katy M; Liang, Furong; Kaciroti, Niko; Zhao, Gengli; Santos, Denise CC; Zhang, Zhixiang; et al.
Abstract: Background: Previous trials of iron supplementation in infancy did not consider maternal iron supplementation. Objective: This study assessed effects of iron supplementation in infancy and/or pregnancy on infant iron status, illnesses, and growth at 9 mo. Methods: Enrollment occurred from December 2009 to June 2012 in Hebei, China. Infants born to women in a pregnancy iron supplementation trial were randomly assigned 1:1 to iron [∼1 mg Fe/(kg · d) as oral iron proteinsuccynilate] or placebo from 6 wk to 9 mo, excluding infants with cord ferritin <35 μg/L. Study groups were pregnancy placebo/infancy placebo (placebo/placebo), pregnancy placebo/infancy iron (placebo/iron), pregnancy iron/infancy placebo (iron/placebo), and pregnancy iron/infancy iron (iron/iron). The primary outcome was 9-mo iron status: iron deficiency (ID) by cutoff (≥2 abnormal iron measures) or body iron <0 mg/kg and ID + anemia (hemoglobin <110 g/L). Secondary outcomes were doctor visits or hospitalizations and weight or length gain from birth to 9 mo. Statistical analysis by intention to treat and dose-response (between number of iron bottles received and outcome) used logistic regression with concomitant RRs and general linear models, with covariate control as applicable. Results: Of 1482 infants randomly allocated, 1276 had 9-mo data ( n = 312–327/group). Iron supplementation in infancy, but not pregnancy, reduced ID risk: RRs (95% CIs) were 0.89 (0.79, 0.998) for placebo/iron compared to placebo/placebo, 0.79 (0.63, 0.98) for placebo/iron compared to iron/placebo, 0.87 (0.77, 0.98) for iron/iron compared to placebo/placebo, and 0.86 (0.77, 0.97) for iron/iron compared to iron/placebo. However, >60% of infants still had ID at 9 mo. Receiving more bottles of iron in infancy was associated with better infant iron status at 9 mo but only among iron-supplemented infants whose mothers were also iron supplemented (i.e., the iron/iron group). There were no group differences in hospitalizations or illnesses and no adverse effects on growth overall or among infants who were iron sufficient at birth. Conclusions: Iron supplementation in Chinese infants reduced ID at 9 mo without adverse effects on growth or illness. Effects of iron supplementation in pregnancy were observed only when higher amounts of iron were distributed in infancy. This trial was registered at clinicaltrials.gov as NCT00613717.